Penerapan Metode Naive Bayes Untuk Prediksi Kelulusan Mahasiswa Tepat Waktu Di Prodi Sistem Informasi Universitas Pamulang - Risah Subariah; Afrizal Zein (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2023)
Abstract This study analyzes historical data using the Naive Bayes algorithm to predict how many new students will complete education on time. This method was chosen because it is able to study previous case data used as test data. Of the many traits marked in this study, some of them are national exams, such as the National Examination. Other attributes include gender, school and area of ​​origin, family income and parents' occupation. Additionally, the number of siblings a person has is taken into account. By analyzing the new data, a lecturer can determine whether students have time to complete their studies or not. This research has produced a decision support system application with an accuracy rate of close to 85%. Keywords: Prediction of On Time Graduation, Naive Bayes Method, Data Mining